Integrating Ligand-Receptor Interactions and In Vitro Evolution for Streamlined Discovery of Artificial Nucleic Acid Ligands - Hasan E. Zumrut; Sana Batool; Kimon V. Argyropoulos; Nicole Williams; Roksana Azad; Prabodhika R. Mallikaratchy (Elsevier, 2019)
To discover DNA ligands against a predetermined receptor protein complex, we introduce a comprehensive version of ligand-guided selection (LIGS). LIGS is, itself, a variant of systematic evolution of ligands by exponential enrichment (SELEX). Herein, we have optimized LIGS to identify higher affinity aptamers with high specificity. In addition, we demonstrate the expandability of LIGS by performing specific aptamer elution at 25°C, utilizing multiple monoclonal antibodies (mAbs) against cultured cells and primary cells obtained from human donors expressing the same receptor. Eluted LIGS libraries obtained through Illumina high-throughput (HT) DNA sequencing were analyzed by bioinformatics tools to discover five DNA aptamers with apparent affinities ranging from 3.06 ± 0.485 nM to 325 ± 62.7 nM against the target, T cell receptor-cluster of differentiation epsilon (TCR-CD3ε) expressed on human T cells. The specificity of the aptamers was validated utilizing multiple strategies, including competitive binding analysis and a double-knockout Jurkat cell line generated by CRISPR technology. The cross-competition experiments using labeled and unlabeled aptamers revealed that all five aptamers compete for the same binding site. Collectively, the data in this report introduce a modified LIGS strategy as a universal platform to identify highly specific multiple aptamers toward multi-component receptor proteins in their native state without changing the cell-surface landscape. Keywords: Aptamers, SELEX, ligands, LIGS, CD3epsilon, T cells, nucleic acids